1993
DOI: 10.1128/iai.61.4.1385-1394.1993
|View full text |Cite
|
Sign up to set email alerts
|

Immunization of virgin cows with surface antigen TF1.17 of Tritrichomonas foetus

Abstract: Protection by surface antigen TF1.17 of Tritrichomonas foetus was investigated because it reacted with a monoclonal antibody which immobilized and mediated complement killing of the organism and prevented adherence to vaginal epithelial cells. This monoclonal antibody was used to demonstrate conservation of the antigen in most strains and to immunoaffinity purify the 50- to 70-kDa glycoprotein antigen. In preparation for immunization studies, the appropriate challenge dose of parasites was determined by intrav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
0
5

Year Published

1994
1994
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 16 publications
3
63
0
5
Order By: Relevance
“…Cows and heifers with no previous T. foetus contact can be infected with as low as 100-200 motile cells in the anterior vagina. 11,13,15 Vaginitis, endometritis and reproductive failure result. 15,16 The fetus is typically lost between 9 and 20 weeks of the 40-week gestation period, 11,17,18 but sometimes third trimester losses occur.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cows and heifers with no previous T. foetus contact can be infected with as low as 100-200 motile cells in the anterior vagina. 11,13,15 Vaginitis, endometritis and reproductive failure result. 15,16 The fetus is typically lost between 9 and 20 weeks of the 40-week gestation period, 11,17,18 but sometimes third trimester losses occur.…”
Section: Introductionmentioning
confidence: 99%
“…30 The mAbs also reacted strongly with T. foetus LPG. 29 Therefore, Mab TF1.17 was used to immunoaffinity purify a highly glycosylated surface antigen, referred to as TF1.17 antigen, 13 with similar lipid and monosaccharide composition to T. foetus LPG. 31…”
Section: Introductionmentioning
confidence: 99%
“…In a more recent study from Argentina, several heifers remained infected up to 300 days after breeding (Mancebo et al, 1995). Parsonson et al (1976), Skirrow and BonDurant (1990), BonDurant et al (1993), Anderson et al (1996)…”
Section: Reservoir Animal Speciesmentioning
confidence: 96%
“…This glycosylated surface antigen was later shown to be a lipophosphoglycan (LPG)/protein complex. Systemic immunization with the immunoaffinity-purified LPG-containing surface antigen, followed by intravaginal challenge with T. foetus, resulted in significantly earlier clearance of the parasite from vaccinated animals than from controls (BonDurant et al, 1993;Corbeil et al, 2001). More importantly, clearance of immunized animals most often occurred before 7 weeks of infection.…”
Section: Trichomoniasismentioning
confidence: 98%
“…Older bulls have deeper epithelial crypts, which may have lower oxygen tension. In order to understand protective acquired immune responses, monoclonal antibodies (mAbs) with putative protective functions were chosen for immunoaffinity purification of a highly glycosylated surface antigen (BonDurant et al, 1993;Corbeil et al, 2001). Analysis of many isolates of T. foetus indicated that two mAbs recognized different epitopes of the same antigen, which was conserved in all isolates tested.…”
Section: Trichomoniasismentioning
confidence: 99%